Propuesta de remediación de aguas del lago Sochagota según parámetros de salinidad (2023)
The purpose of this document is to propose a conceptual strategy for the remediation of the water of Lake Sochagota through methods or technologies applicable to the site, methods in which they will be based on their adaptability to the geographical area and the remission efficiencies that they present to various organic, inorganic and biological contaminants. For the development of this strategy, we started from current technologies and/or methods which are applied in bodies of surface water such as lakes and rivers. The feasibility was also taken into account when applying these technologies since the Lake Sochagota is in the process of being a protected natural area, so modifying its landscape is not viable.